Diamondback moth Plutella xylostella L. (Lepidoptera: Plutellidae) and its natural enemies: Population fluctuations and influence of biotic and abiotic factors - Massarolli, Angélica; Butnariu , Alessandra Regina; Pereira , Mônica Josene Barbosa; Dallacort, Rivanildo; Costa , Valmir Antonio; Shimbori , Eduardo Mitio; Moura, Mauricio Osvaldo; Foerster , Luís Amilton (Acta Scientiarum. Biological Sciences, 2024)
The annual worldwide costs associated with the diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae), are estimated to be between four and five billion dollars in yield losses and management costs. Studies aimed at better understanding this pest and its natural enemies are essential for the development of new control strategies to increase production and meet world demand for healthy foods produced in ways that protect the environment for future generations. The present study was aimed at (i) describing population fluctuations of P. xylostella in collard greens, (ii) identifying its larval parasitoids, and (iii) evaluating biotic and abiotic factors that affect the population dynamics of this pest and its parasitoids in commercially grown collard greens in the municipality of Tangará da Serra, Mato Grosso State, Brazil. Fluctuations in the population of P. xylostella were assessed from March 2016 to February 2017. During 12 months of sampling, 4,310 larvae and pupae were collected, of which 640 (15%) were parasitized by native natural enemies. Three species of larval parasitoids were observed: Oomyzus sokolowskii (Kurdjumov) (Hymenoptera: Eulophidae), Apanteles piceotrichosus Blanchard and Cotesia sp. (Hymenoptera: Braconidae). Precipitation and release of the egg parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) were the factors that most influenced the population fluctuations of P. xylostella. Also, native parasitoids were affected by the use of non-selective insecticides. Our findings are a contribution to the understanding of interactions between this pest and its environment to improve control strategies and preserve biodiversity.